2015
DOI: 10.1097/wad.0000000000000002
|View full text |Cite
|
Sign up to set email alerts
|

Reelin Signaling Pathway Genotypes and Alzheimer Disease in a Spanish Population

Abstract: Our data suggest a possible relation between certain reelin signaling pathway genotypes and cognitive impairment related to AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 7 publications
2
22
1
Order By: Relevance
“…The RELN genotype distribution observed in our control sample is similar to earlier reports on other Caucasian control populations (Bufill et al, 2013;Seripa et al, 2008;Kramer et al, 2011). In a Spanish case-control study rs2299356 polymorphism was found to be associated with AD and rs528528 with mild cognitive impairment (Bufill et al, 2013).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The RELN genotype distribution observed in our control sample is similar to earlier reports on other Caucasian control populations (Bufill et al, 2013;Seripa et al, 2008;Kramer et al, 2011). In a Spanish case-control study rs2299356 polymorphism was found to be associated with AD and rs528528 with mild cognitive impairment (Bufill et al, 2013).…”
Section: Discussionsupporting
confidence: 74%
“…Despite its expected important role in neurodegeneration, according to our knowledge so far only three studies have examined genetic associations of RELN with AD, and one with AD-related neuropathology (Seripa et al, 2008;Antoniades et al, 2011;Kramer et al, 2011;Bufill et al, 2013). This study aimed to replicate the previous reports on associations between RELN single nucleotide polymorphisms (SNP) and AD in an independent sample.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Seven SNPs typed from the CAMK2A gene were found to be significantly associated with alcohol dependence [113]. Notably, the rs10463293 SNP has previously been associated with working memory performance [122], while SNP rs3756577 has been suggested 21 before to influence the risk for Alzheimer's disease [123]. A set of 13 CAMK2A SNPs were found to predict the number of alcohol drinking days per month in a sample of adults living in the US [124].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cyclin B, the expression of PLKs ( Drosophila polo homologues) is upregulated in susceptible hippocampal and cortical neurons of AD patients [44, 45]. A significant association between the genotypes of PLK2 (rs15009 and rs702723) was found in AD [46]. Mechanism study shows PLK1 is elevated during the cell-cycle re-entry of neuronal cells in vitro [47].…”
Section: Discussionmentioning
confidence: 99%